PLANNING FOR THE ARRANGEMENT OF PUBLIC STREET LIGHTS (PJU) IN BENGKAYANG DISTRICT - Supriatna, Muhammad Farhan; Arsyad, Muhammad Iqbal; Danial, Danial (Faculty of Engineering, Universitas Tanjungpura, 2024)
Public street lighting (PJU) is a public lighting installation that is commonly installed on a street medium, bridges or in certain places such as parks and other public places. The aim of this research is to make the layout of public street lighting lights to be more optimal, efficient and in accordance with the standardization of BSN SNI 7391:2008. The planning of the installation of the PJU lamps is carried out prior to the field observation of the existing conditions followed by the installation process. On the highway of Bengkayang has a total length of road 22,550 metres and only about 17,850 meters that has already installed PJU of 447 points of light and that lives only 318 points with the use of light type SON-T 150 watt, SON- T 250 watt and LED 60 watt. The interpolar distance is an average of 40 meters as well as the width of the road 6 meters and 4 meters, the resulting lighting has met and slightly exceeded the standard. Based on the results of the planning, optimization of the existing road length 17,850 meters and the addition of light points of 4,700 meters in the road and corridors that have not yet had street lighting, so that the total length of the road 22,550 metres and 568 light points are divided into 2 classes of road i.e. primary and local collectors. The total energy consumption of 568 lamps is 584.4 kWh per day and is 6.54 per cent more efficient than the current 625,32 kWh of 318 lamps per day, despite an increase in the number of lamps of 250 points.